A petrographic, geochemical and geochronological investigation of deformed granitoids from SW Rajasthan : Neoproterozoic age of formation and evidence of Pan-African imprint - Solanki, Anika M. (My University, 2011)
Granitoid intrusions are numerous in southwestern Rajasthan and are useful because they can provide geochronological constraints on tectonic activity and geodynamic conditions operating as the time of intrusion, as well as information about deeper crustal sources. The particularly voluminous Neoproterozoic felsic magmatism in the Sirohi region of Rajasthan is of particular interest as it may have implications for supercontinental (Rodinia and Gondwana) geometry. The Mt. Abu granitoid pluton is located between two major felsic suites, the older (~870-800 Ma) Erinpura granite and the younger (~751-771 Ma) Malani Igneous Suite (MIS). The Erinpura granite is syn- to lateorogenic and formed during the Delhi orogeny, while the MIS is classified as alkaline, anorogenic and either rift- or plume-related. This tectonic setting is contentious, as recent authors have proposed formation within an Andean-type arc setting. The Mt. Abu granitoid pluton has been mapped as partly Erinpura (deformed textural variant) and partly younger MIS (undeformed massive pink granite). As the tectonic settings of the two terranes are not compatible, confusion arises as to the classification of the Mt. Abu granitoid pluton. Poorly-constrained Rb-Sr age dating place the age of formation anywhere between 735 ± 15 and 800 ± 50 Ma. The older age is taken as evidence that the Mt. Abu intrusion was either a late phase of the Erinpura granite. However, U-Pb zircon geochronology clearly indicates that the Mt. Abu felsic pluton is not related to- or contiguous with- the Erinpura granite suite. The major results from this study indicate that the all textural variants within the Mt. Abu pluton were formed coevally at ~765 Ma. Samples of massive pink granite, mafic-foliated granite and augen gneiss from the pluton were dated using U-Pb zircon ID-TIMS at 766.0 ± 4.3 Ma, 763.2 ± 2.7 Ma and 767.7 ± 2.3 Ma, respectively. The simple Mt. Abu pluton is considered as an enriched intermediate I- to A-type intrusion. They are not anorogenic A-types, as, although these felsic rocks have high overall alkali and incompatible element enrichment, no phase in the Mt. Abu pluton contains alkali rich amphibole or pyroxene, nor do REE diagrams for the most enriched samples show the gull-wing shape typical of highly evolved alkaline phases. The alkali-enriched magma may be explained by partial melting of a crustal source such as the high-K metaigneous (andesite) one suggested by Roberts & Clemens (1993), not derivation from a mantle-derived mafic magma. The fairly restricted composition of Mt. Abu granitoids suggests that partial melting and a degree of assimilation/mixing may have been the major factors affecting the evolution of this granitoid pluton; fractional crystallization was not the major control on evolution of these granitoids. Revdar Rd. granitoids that are similar in outcrop appearance and petrography to Mt. Abu granitoids also conform to Mt. Abu granitoids geochemically and are classified as part of the Mt. Abu felsic pluton. Mt. Abu samples from this study have a maximum age range of 760.5-770 Ma, placing the Mt. Abu pluton within the time limits of the Malani Igneous Suite (MIS) as well as ~750 Ma granitoids from the Seychelles. Ages of the Sindreth-Punagarh Groups are also similar. These mafic-ultramafic volcanics are thought to be remnants of an ophiolitic mélange within a back-arc basin setting at ~750-770 Ma. The three Indian terranes are spatially and temporally contiguous. The same contiguity in space and time has been demonstrated by robust paleomagnetic data for the Seychelles and MIS. These similarities imply formation within a common geological event, the proposed Andean-type arc (Ashwal et al., 2002) on the western outboard of Rodinia. The implications are that peninsular India did not become a coherent entity until after this Neoproterozoic magmatism; Rodinia was not a static supercontinent that was completely amalgamated by 750 Ma, as subduction was occurring here simultaneous with rifting elsewhere. Pageiv The Mt. Abu pluton has undergone deformation, with much of the pluton having foliated or augen gneiss textures. The timing of some of the deformation, particularly the augen gneiss and shear zone deformation, is thought to have occurred during intrusion. The Mt. Abu and Erinpura granitoids have experienced a common regional metamorphic event, as hornblende (Mt. Abu) and biotite (Erinpura) give 40Ar/39Ar ages of 508.7 ± 4.4 Ma and 515.7 ± 4.5 Ma, respectively. This event may have reactivated older deformatory trends as well. The temperature of resetting of argon in hornblende coincides with temperatures experienced during upper-greenschist to lower-amphibolite facies metamorphism. These late Pan-African ages are the first such ages reported for the Sirohi region and southern part of the Aravalli mountain range. They offer evidence for the extension of Pan-African amalgamation tectonics (evidence from southern India) into NW India. The age of formation of the Erinpura augen gneiss magma is 880.5 ± 2.1 Ma, thus placing the Erinpura granitoids within the age limits of the Delhi orogeny (~900-800 Ma; Bhushan, 1995). Most deformation observed here would have been caused by compression during intrusion. The Erinpura granitoids are S-type granitoids due to their predominantly peraluminous nature, restricted SiO2-content, normative corundum and the presence of Al-rich muscovite and sillimanite in the mode. Weathered argillaceous metasedimentary material may also have been incorporated in this magma, while the presence of inherited cores suggests relatively lower temperatures of formation for these granitoids as compared to the Mt. Abu granitoids. The age of inheritance (1971 ± 23 Ma) in the Erinpura augen gneiss is taken as the age of the source component, which coincides with Aravalli SG formation. The Sumerpur granitoids differ from the Erinpura granitoids in terms of macroscopic and microscopic texture (undeformed, rarely megaporphyritic) but conform geochemically to the Erinpura granitoid characteristics and may thus be related to the Erinpura granitoid suite.The Revdar Rd. granitoids that are similar in macroscopic appearance to Erinpura granitoids also conform geochemically, and may similarly belong to the Erinpura granite suite. A Revdar Rd. mylonite gneiss with the Erinpura granitoids’ geochemical signature was dated at ~841 Ma, which does not conform to the age of the type-locality Erinpura augen gneiss dated here, but later intrusion within the same event cannot be ruled out because of the uncertainty in the age data (~21 Ma). The presence of garnet in one Revdar Rd. (Erinpura-type) sample implies generation of these granitoids at depth and/or entrainment from the source, similar to the S-type Erinpura granitoids. The Ranakpur granitoids differ significantly from both the Erinpura and Mt. Abu intrusives due to their low SiO2-content and steep REE profiles (garnet present in the source magma); they are thought to have been generated under higher pressures from a more primitive source. The deeper pressure of generation is confirmed by the absence of a negative Eu-anomaly. The Ranakpur quartz syenite dated at 848.1 ± 7.1 Ma is younger by ~30 m.y. than the Erinpura augen gneiss. It is within the same time range as numerous other granitoids from this region as well as the Revdar Rd. granitoid dated in this study. The prevalence of 830- 840 Ma ages may indicate that a major tectonic event occurred at this time. The Ranakpur quartz syenite may have been generated near a subduction or collision zone, where thickened crust allows for magma generation at depth. The deeply developed Nb-anomaly in the spider diagram also implies a larger subduction component to the magma. The Swarupganj Rd. monzogranite is interpreted to have formed by high degrees of partial melting from a depleted crustal source and is dissimilar to other granitoids from this study. More sampling, geochemical and geochronological work needs to be done in order to characterize this intrusion. Pagev The Kishengarh nepheline syenite gneiss is situated in the North Delhi Fold Belt and is the oldest sample dated within this study. The deformation in this sample is due to arc- or continental- collision during a Grenvillian-type orogeny related to the amalgamation of the Rodinia supercontinent (and peninsular India), dated by the highly reset zircons at ~990 Ma. This is considered a DARC (deformed alkaline rock and carbonatite) and represents a suture zone (Leelanandam et al., 2006). The primary age of formation of this DARC is older than 1365 ± 99 Ma, which is the age of xenocrystic titanites from the sample. The granitoid rocks from this study area (Sirohi region) range widely in outcrop appearance, petrography and geochemistry. Granitoids from the Sirohi region dated in this study show a range of meaningful ages that represent geological events occurring at ~880 Ma, ~844 Ma, ~817 Ma, ~789 Ma, ~765 Ma and ~511 Ma. Granitoid magmatism (age of formation) in this region is predominantly Neoproterozoic, and the number of events associated with each granitoid intrusion as well as diverse tectonic settings implies a complexity in the South Delhi Fold Belt that is not matched by the conventional and simplified view of a progression from collision and orogeny during Grenvillian times (Rodinia formation), through late orogenic events, to anorogenic, within-plate (rift-related) alkaline magmatism during Rodinia dispersal. Instead, it is envisaged that convergence and subduction during the formation of Rodinia occurred at ~1 Ga (Kishengarh nepheline syenite deformation), with a transition to continental-continental collision at ~880-840 Ma (Erinpura and Ranakpur granitoids). This was then followed by far-field Mt. Abu and MIS magmatism, related to a renewed period of subduction at ~770 Ma. The last deformatory event to affect this region was that associated with the formation of Gondwana in the late Pan-African (~510 Ma).
MSc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Plate tectonics; Continental drift; Continental margins; Formations (Geology); Rifts (Geology); Geology, Stratigraphic (Paleozoic)